Effects of music training using glockenspiel on the development of children's phonological awareness skills - Pastor, Mylene Dela Fuente (College of Education, University of the Philippines Diliman, 2015)
This research attempted to find out whether there is a significant difference in the phonological awareness skills of Grade 1 students from a city public school before and after a music training using glockenspiel (lyre), in terms of: (1) orally segmenting a two to three-syllable word into its syllabic parts, (2) blending spoken syllables to form a word, (3) providing the beginning consonant sound of a given word, (4) identifying rhyming words in nursery rhymes and simple poems, and (5) giving the new spoken word when a specified phoneme is added, removed or changed. In addition, the study looked into the children’s music training responses that suggest development of their phonological awareness skills. Through purposive sampling, a Grade 1 class of 41 students was identified as sample for this study. They took an aural pretest in Filipino on the phonological awareness skills mentioned above in order to identify 10 participants with the lowest pretest scores. These 10 participants attended a 40-session music training using the glockenspiel instrument, with each session consuming 20 minutes. They were taught to play a simple music piece every five sessions and were also observed for any music training response related to the five phonological awareness skills mentioned. They were observed and their progress was recorded. In the end, they took an aural posttest in Filipino on the same phonological awareness skills. Based on the results of the aural pretest and posttest, as computed using Wilcoxon T test for correlated samples, it was found that there is a significant difference in children’s phonological awareness skills before and after the music training using glockenspiel, in terms of: (1) orally segmenting a two to three-syllable word into its syllabic parts, (2) blending spoken syllables to form a word, and (3) providing the beginning consonant sound of a given word. On the other hand, results of the PA skills of identifying rhyming words in nursery rhymes and simple poems, and giving the new spoken word when a specified phoneme is added, removed or changed can neither reject the null hypotheses nor accept the alternative hypotheses of the current research due to small sample size with nonzero difference scores. As regards children’s music training responses, it was found that there were certain responses, such as initially playing the musical pitches in a manner that is slow and detached from each other, eventually playing the musical pitches in a manner that is faster and connected with each other, identifying the initial musical pitch of a melodic line, and recognizing similar musical pitches and melodic lines, that suggest development on the following phonological awareness skills: (1) orally segmenting a two to three-syllable word into its syllabic parts, (2) blending spoken syllables to form a word, (3) providing the beginning consonant sound of a given word, and (4) identifying rhyming words in nursery rhymes and simple poems. On the other hand, there was no music training response relevant to the phonological awareness skill of giving the new spoken word when a specified phoneme is added, removed or changed.